Internet of things : evolutions and innovations - Bouhaï, Nasreddine; Saleh, Imad, 1960- (Digital tools and uses set ;, 2017)
The development of connected, communicating objects is showing no signs of slowing down. With an increasing number of objects available on the market, the evolution of the Internet of Things is leading to more and more fields being explored via information and communication sciences. This book analyzes the ecosystem of the Internet of Things by retracing the historical and technological context of the Internet's evolution from traditional to dynamic, social and semantic, and then towards this ecosystem of connected objects. The evolution of concepts surrounding the Internet of Things is explored via real-life examples of connected objects; both those used for specific functions and for more general everyday objects. Numerous issues associated with these new technological and digital transformations in a "hyperconnected" world, as well as the impact of the massive influx of connected objects, are discussed. The crucial questions of potential intrusion into the private lives of users as well that of security are then studied